2020
DOI: 10.3823/840
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Pseudomonas aeruginosa isolates from various clinical specimens in Khartoum/Sudan: Antimicrobial resistance and virulence genes

Abstract: Background: Pseudomonas aeruginosa is a pathogenic organism responsible for frequent wound and nosocomial infections worldwide. Its infections are difficult to control since the organism is known to rapidly develop antibiotic resistance and becomes multidrug-resistant (MDR) during treatment of patients. Aim of the study: This study was intended to investigate the occurrence of certain important types of (ESBL) and (MBL) enzymes in association with important specific virulence factors  associated with P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…Our findings reveal gentamicin to be the most effective antibiotic, with varying degrees of susceptibility to this antibiotic observed from Miami (50%) and Kadangaru (40%) isolates. This observation is in agreement with the high susceptibility (84% and 81.6%) to gentamicin reported by earlier studies conducted in Pakistan 26 and Sudan 5 respectively. This phenomenon may be predicated on the reduced administration of gentamicin in those regions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings reveal gentamicin to be the most effective antibiotic, with varying degrees of susceptibility to this antibiotic observed from Miami (50%) and Kadangaru (40%) isolates. This observation is in agreement with the high susceptibility (84% and 81.6%) to gentamicin reported by earlier studies conducted in Pakistan 26 and Sudan 5 respectively. This phenomenon may be predicated on the reduced administration of gentamicin in those regions.…”
Section: Discussionsupporting
confidence: 93%
“…These bacteria have been largely implicated in nosocomial infections. 5 Nosocomial infections associated with P. aeruginosa include but not limited to bacteremia, burn infection, cystic fibrosis, pneumonia and urinary tract infection. 6 Sadly, bacteremia caused by this bacterium is often associated with high mortality when compared with other Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, colistin sulphate and kanamycin resistance was the least observed in both clinical and environmental isolates respectively. This agrees with other studies who studied aminoglycosides resistance in clinical and environmental isolates 33,34 . Vitek 2 compact system as an e cient diagnostic tool gave the explicit identities of isolates and con rmed the antibiogram pro les of previously screened MDR isolates and revealed other resistance phenotypes, several other pathogens that could not be tentatively identi ed with conventional biochemical tests were also detected.…”
Section: Discussionsupporting
confidence: 93%
“…Due to the limited studies on clinical pseudomonas isolates in Libya, we can’t assert that the dissemination of bla TEM , bla SHV-1 or bla CTXM is lower in them compared to Enterobacteriaceae . However, a study in Sudan, a neighboring country, had shown low distribution rates of ESBL genes among P. aeruginosa clinical isolates [ 32 ]. In their study, the distribution rate of selected ESBL genes among 70 P. aeruginosa isolates was 6.6% for bla CTXM , 10% for bla SHV-1 and 3.3% for bla TEM , which are in line with our findings.…”
Section: Discussionmentioning
confidence: 99%